Perancangan Prototipe Sistem Informasi Sejarah dan Wisata Kota Depok Berbasis Web - Mahesa, Gusnul; Azhar, Nur Chalik; Darmawan, Rio Musa; Syauqy, Muhammad Faris; Bukhori, Ahmad; Rahman, Abdul (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
The city of Depok has a wealth of historical value and tourism potential that has not been properly documented in digital media. The lack of access to related media causes difficulties for the community and tourists. This study aims to design a web-based information system prototype that presents comprehensive and engaging historical and tourism information about the city of Depok. The method used is a descriptive approach, beginning with the stages of needs analysis, system design, and user interface design. The results of this study are interactive visual prototype designs that include historical information and a list of tourist locations. This prototype has been successfully developed and tested, showing positive results in supporting the preservation of history and promotion of tourism in Depok City. User testing using the System Usability Scale (SUS) method resulted in an average score of 89.84, which falls into the ‘Excellent’ category. With this achievement, this digital information system can serve as a starting point for further extensive and sustainable development.